Implementation of Local Context Vocabulary Exposure in Teaching English at SMP Negeri 1 Padaido Biak Regency - Krisifu, Adolfina (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2019)
The study aims at investigating the effect of local content vocabulary exposure in teaching English at SMPN 1 Padaido Biak Regency. This study employed a descriptive study and total sampling conducted to 75 students (from the first to third grades) of SMP Negeri 1 Mbromsi, in Aimando subdistrict, Padaido islands of Biak Regency. Data were gained from students’ results of pre and post tests on vocabulary relating to things near them or familiar to them like things in the sea. The result shows that the implementation of contextual teaching and learning have brought influence to students’ vocabulary achievement since the approach allows teachers to creatively produce their learning materials that accommodate students’ learning needs based on school and home environments as well as to develop freely their pedagogical techniquest in fun ways.